FAKTOR-FAKTOR YANG MEMPENGARUHI LAPORAN KEUANGAN UMKM DI PEKALONGAN DENGAN PEMANFAATAN INFORMASI AKUNTANSI SEBAGAI VARIABLE INTERVENING - M. Iqbal Notoatmojo; Rizka Ariyanti; Ali Imron (Jurnal Aplikasi Akuntansi, 2023)
This study examines The impact of the business duration, business size, and business revenue on financial statements by including the use of Accounting data serving as an intermediate variable for MSMEs in the district. Pekalongan. The population comprises all MSMEs in Pekalongan Regency, and 100 respondents were randomly selected using the Probability Sampling method. Information was gathered by employing a survey questionnaire and analysis using the path analysis assisted by SPSS software. The study's outcomes on the length of business do not affect the utilization of accounting information. Business Scale and Business Turnover have a significant influence on the Utilization of Accounting Information. Utilization of Accounting Information does not affect the Financial Statements. The length of business, business scale, and business turnover positively and significantly impact the Financial Statements and have no indirect impact on the financial reports through the Utilization of Accounting Information. This indicates that the Utilization of Accounting Information is considered unable or unable to act as an intermediary in influencing the variables of Business Duration, Business Size, and Business Revenue on Financial Statements